The Influence of Good Corporate Governance and Corporate Social Responsibility Disclosure on Financial Distress Risk (Study on Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange for the 2021-2023 Period) - Athena Salesya Alzaira; Dwi Urip Wardoyo (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) disclosure on the risk of Financial Distress in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. GCG is measured using three indicators: institutional ownership, managerial ownership, and independent commissioners. CSR disclosure is measured based on the Global Reporting Initiative (GRI) standards, while Financial Distress is analyzed using the Altman Z-Score method. The research employs a quantitative approach with panel data regression analysis. Data were collected from annual and sustainability reports of the companies included in the sample. The results indicate that, partially, independent commissioners and CSR disclosure have a significant negative effect on Financial Distress. Meanwhile, institutional ownership and managerial ownership do not show a significant effect. Simultaneously, the four independent variables significantly influence the risk of Financial Distress. These findings suggest that implementing strong corporate governance and maintaining a solid commitment to CSR practices can enhance financial stability and reduce the potential for financial distress. This research is expected to contribute to the development of risk management strategies and strategic decision-making within the property and real estate sector.